ANALYSIS OF THE DIGITAL COMPETENCE OF MACHINING VOCATIONAL SCHOOL TEACHERS IN GORONTALO - Hendra Uloli; Mohamad Riyandi Badu (UNIVERSITAS SRIWIJAYA, 2023)
Digitalization in various fields is unavoidable. However, gaps still occur, starting from infrastructure and access to digital competence, which is still low. This also happens in the world of education, where the digital maturity level of teachers is still low. This study aims to describe the digital competence of mechanical engineering vocational high school teachers in Gorontalo Province. This research uses a quantitative approach with descriptive data analysis. The results found that the teacher's digital competence is in the